Oscillation-Based Test in Mixed-Signal Circuits - Huertas Sánchez, Gloria; Vázquez García de la Vega, Diego; Rueda Rueda, Adoración; Huertas Díaz, Jose Luis (Frontiers in Electronic Testing, 2006)
Oscillation-Based Test in Mixed-Signal Circuits presents the development and experimental validation of the structural test strategy called Oscillation-Based Test - OBT in short. The results here presented allow to assert, not only from a theoretical point of view, but also based on a wide experimental support, that OBT is an efficient defect-oriented test solution, complementing the existing functional test techniques for mixed-signal circuits.